A high prevalence of human T-lymphotropic virus (HTLV 1/2) infection among Afro-descendants, Esmeraldas province, Ecuador – need for the implementation of surveys and control programs - Mosquera-Herrera CE; Aspiazu-Miranda EP; de Waard JH; Garcia-Bereguiain MA (Infection and Drug Resistance, 2019)
Carmen Eulalia Mosquera-Herrera1,2, Elvia Piedad Aspiazu-Miranda1,2, Jacobus Henri de Waard3,4, Miguel Angel Garcia-Bereguiain3,51Laboratorio de Virología, Instituto Nacional de Salud Pública e Investigación “Leopoldo Izquieta Pérez”, Guayaquil, Ecuador; 2Facultad de Ciencias Médicas, Universidad de Guayaquil, Guayaquil, Ecuador; 3One Health Research Group, Facultad de Ciencias de la Salud, Universidad de Las Américas, Quito, Ecuador; 4Servicio Autónomo Instituto de Biomedicina, Universidad Central de Venezuela, Caracas, Venezuela; 5School of Biological Sciences and Engineering, Yachay Tech University, Urcuquí, EcuadorBackground: Infection with the Human T-cell lymphotropic virus (HTLV) type 1 and 2 is endemic in South America. Although there are reports of the presence of these retroviruses in Ecuador, the infection is usually neglected in healthcare settings and by public health authorities, and no actualized prevalence data are available.Objectives: This cross-sectional study aimed to estimate, using for the first time to our knowledge in Ecuador immunological and molecular biology methodologies, the prevalence of HTLV-1/2 infection in asymptomatic individuals from a potentially high-risk population of Afro-Ecuadorians in the Province of Esmeraldas.Study design: Two hundred and twenty-seven plasma samples from asymptomatic individuals were analyzed for the detection of the HTLV-1/2 virus with three methods: a commercial ELISA, an indirect immunofluorescence (IF) assay, and a nested-PCR.Results: The overall prevalence of HTLV-1/2 antibodies in this population, as determined with an ELISA, was 11.0%. Both the IF assay and the nested-PCR confirmed a prevalence of 3.5%.Conclusion: The high prevalence of HTLV-1/2 infection among the Afro-Ecuadorian population of Esmeraldas Province shows the need of the implementation of control and prevention interventions to overcome the further dissemination of the infection. To define the real problem of HTLV-1/2 infection in Ecuador, more prevalence studies have to be undertaken in other Afro-Ecuadorian populations and high-risk populations like the indigenous population of the Andes Mountains and the tropical Amazon region.Keywords: HTLV 1, HTLV2, Afro-descendants, Ecuador, ELISA, PCR